Is it possible to prevent chemotherapy-induced heart failure with cardiovascular drugs - the review of the current clinical evidence - Korzeniowska K; Jankowski J; Cieślewicz A; Jabłecka A (Dove Medical Press, 2019)
Katarzyna Korzeniowska, Jerzy Jankowski, Artur Cieślewicz, Anna Jabłecka Department of Clinical Pharmacology, Poznan University of Medical Sciences, Poznan 61-848, PolandCorrespondence: Artur CieślewiczDepartment of Clinical Pharmacology, Poznan University of Medical Sciences, Długa 1/2 Str., Poznan 61-848, PolandTel +48 61 854 9216Fax +48 61 853 3161Email artcies@ump.edu.plAbstract: Cardiovascular diseases and cancer are the most common death causes in the USA and Europe. Moreover, many patients suffer from both of these conditions – a situation which may result from cardiotoxicity of anticancer treatment. In order to reduce the severity of this adverse effect, various methods have been proposed, including the usage of new drug forms and less toxic analogs, omitting the combinations of potentially cardiotoxic drugs and introducing potential cardioprotective agents to the therapy. However, prevention of cardiotoxicity still seems to be insufficient. The article reviews the results of current studies on the use of cardiovascular drugs in the prevention of cardiotoxicity. Based on this knowledge, the most promising cardioprotective drugs seem to be carvedilol, nebivolol, enalapril, and candesartan, as they prevent heart remodeling and correct elevated resting heart rate, which directly affects mortality. Alternatively, in case of adverse reactions, statins might be considered.Keywords: chemotherapy, cardiotoxicity, heart failure, prevention